Maxillary and Mandibular Interarch Width Among Different Malocclusions - Hiba Tabassum, Sarfaraz Hussain, Sadia Rizwan, Komal Jan, Saima Salman, Munawar Ali Baloch (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the association of maxillary and mandibular interarch width among different malocclusions. Material and Methods: This cross-sectional study was done at the Department of Orthodontics of the Dr. Ishrat Ul Ibad Khan Institute of Oral Health Sciences, Dow University of Health Sciences, Karachi, during a period of one year from January 2017 to December 2017. Individuals with a Class I canine and molar relationship with minor crowding, normal growth and development, and mal-aligned upper and lower dental arches. Class II molar and canine relationship on at least one side, Class II division 1 or 2 groups, bilateral Class III molar relationship in centric occlusion, Class III permanent canine relationship with excessive negative overjet, good facial symmetry, and participants had to have all their permanent teeth present except for their third molars were included. Readings were obtained by measuring the interarch width using a vernier gauge caliper. The calibration of the vernier caliper was checked daily using the standard technique. The intercanine arch width was measured from the cusp tip of one canine to the contralateral canine. Intermolar width was assessed as the distance between the central fossae of the left and right first molars. The readings were taken by a single examiner, and the measurement was repeated three times with an interval of two minutes between each measurement to reduce the possibility of errors. To assess the reliability of the measurements, the intra-examiner reliability was determined using the intraclass correlation coefficient (ICC). The collected data was analyzed using statistical software, SPSS version 26. Results: The study examined the maxillary and mandibular interarch widths of participants with different types of malocclusions. Class I had the highest maxillary intercanine width, and Class III had the highest maxillary intermolar width. Class III had the highest mandibular intercanine and intermolar width. Class II Division 2 had the lowest intercanine and intermolar width in both arches. Significant differences were observed in the mean intermolar width in the mandibular arch between Class II Division 2 and Class III malocclusions and in the maxillary intercanine width between Class I and Class II Division 2 malocclusions. No significant difference was found in other width measurements among the different types of malocclusions. Conclusion: It has been concluded that patients with Class III malocclusion had narrower upper width measurements compared to the normal occlusion sample. Keywords: Maxillary, mandibular, interarch width, malocclusion